THE USE OF STORYTELLING IN TEACHING LISTENING COMPREHENSION AT SMA NEGERI 1 PERCUT SEI TUAN - Hizryanda Ikhsan Harahap; Mahmud Layan Hutasuhut (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
The goals of this research are to analyze students’ comprehension and performance in the listening to storytelling and to find out how the teacher teaching in the classroom. Descriptive qualitative was used as the research methodology. The subjects of the study are a ten year class of SMA Negeri 1 Percut Sei Tuan consisting of 20 students and an English teacher. Observation questionnaires  and documentation review as the research instruments to collect the data. Result of the study revealed that (1) Observing the teacher teach in classroom. (a) The teacher teach is  well because she is made students enjoy listen the story. (b) The teacher motivated the students to actively express their thought. (c) The teacher not only good as a storyteller but also explained clearly by using a gesture. (2) provides questionnaires to students. (d) The students succeeded in comprehending to stories with total score are 85% (3) From students performances in listening to storytelling in descriptive text, students were able to listen several words they often heard.